Pharmacokinetics of Cisplatin and its Metabolites Following Intravenous Administration in Cancer Patients of Bangladesh (KYAMC Journal, 2018)
Background: To determine the mean bioavailability of cisplatin at different time interval after intravenous administration of cisplatin of 18-60 years old 50 male Bangladeshi cancer patients.Materials & Methods: Pharmacokinetic and demographic data were collected from 50 various types of male cancer patients received injection cisplatin 50 mg/m2 infusion for over 3 hours every alternate week for 3 weeks and mean population bioavailability were determined.Results: Statistical analysis from data of HPLC reported that the highest mean plasma concentration of cisplatin was found 428.32 μg/dl (±6.092) after 3 hours and highest mean urinary concentration of cisplatin was found 996.56μg/dl (±1.97) after 12 hours (P